The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/7571742
|View full text |Cite
|
Sign up to set email alerts
|

Self-focusing/Defocusing of Hermite-Sinh-Gaussian Laser Beam in Underdense Inhomogeneous Plasmas

Abstract: The self-focusing/defocusing of Hermite-sinh-Gaussian (HshG) laser beam in underdense inhomogeneous plasmas is studied by using higher-order approximation theory. It is found that Hermite mode index and the fluctuation of the periodic plasma density have a significant effect on the dielectric constant and laser beam self-focusing/self-defocusing. With the increase of mode index, the high-order HshG laser beam is beneficial to suppress self-focusing and enhance self-defocusing. In addition, the effects of decen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Figure 1 reflects the intensity distribution, spatial distribution of the axial and transverse electric field for a shG laser beam in terms of decentred parameter. It is demonstrated that the decentered parameter clearly affects beam width [29].…”
Section: Resultsmentioning
confidence: 98%
“…Figure 1 reflects the intensity distribution, spatial distribution of the axial and transverse electric field for a shG laser beam in terms of decentred parameter. It is demonstrated that the decentered parameter clearly affects beam width [29].…”
Section: Resultsmentioning
confidence: 98%
“…Due to a wide range of potential applications, including laser-driven acceleration, x-ray lasers, harmonic generation, etc, the self-focusing of a powerful laser beam has drawn tremendous interest in the last few decades [1][2][3][4][5][6]. The propagation of powerful laser pulses > I W c m 10 17 2 ( ) / in extremely dense plasmas has seen a sudden spike in demand as a result of the rapid igniter concept for inertial confinement fusion [7].…”
Section: Introductionmentioning
confidence: 99%
“…When a laser beam interacts with plasma, the plasma dielectric constant is adjusted, allowing the electron an oscillatory velocity [11]. Due to the significance of these applications, the non-linear phenomenon (selffocusing) has been explored by various researchers [3,6,7,[10][11][12][13][14][15][16][17][18]. In addition to that Studying the self-focusing of q-Gaussian beams is important for optimizing the design and performance of high-power laser systems, as well as for developing more efficient and effective laser-plasma interaction systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation